Analisis Penyerapan Energi Kinetik pada Berbagai Variasi Kecepatan dan Inersia Flywheel - Faizun, Muhammad Muhtada; Basuki, Hari Arbiantara; Mulyadi, Santoso (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Kinetyc Energy Recovery system (KERS) is a mechanism of non convensional breaking system to absorb and recovery kynetic energy from breaking desseleration by the vehycle asstep of increasing vehichleeficiency. At this moment Kinetyc Energy Recovery system (KERS) are applycated on high speed vehicle, hybrid vehicle, and heavy duty vehicle, usually F1 race car, FerraryEnzo sport car, Flybus and modern truck. The absorbtion of kynetic energy use flywheel. Kynetic energy is effected by flywheel inertia and duration. The purpose of this research is to know absorbtion of kynetic energy from flywheel with 2 various of inertia from KERS type mechanism and wheel velocity various between 800rpm until 1800rpm. This research was done at Design Laboratory of Mechanical Direction Engineering Faculty of Jember University. Conclusion from the research is the biggest absorbtion energy in flywheel from various inertia 0,0317kg.m 2 at 1800rpm are 23.210,72 Joule.Keywords: Kinetyc Energy Recovery system (KERS), flywheel, Inersia, kynetic energy, absorbed energy